Decolonization, neo-apartheid and xenophobic violence in Phaswane Mpe’s welcome to Our Hillbrow - Abdullah, Mustafa Mohammed; Singh, Hardev Kaur Jujar; Abdullah, Omar Mohammed; Hasan, Mohammed Fleih (Universiti Putra Malaysia Press, 2021)
South Africa is undoubtedly one of the most unreceptive destinations in the world for black African refugees due to the prevalent xenophobic violence since the dismantling of apartheid in 1994. Previous research claimed that attitudes of intolerance and xenophobia towards foreigners were results of social and economic insufficiencies. Yet, this study argues that apartheid was not really dismantled, and that incomplete decolonization led to a state of neo-apartheid which catalysed citizens towards aggression and intolerance against foreigners. The article looks at Welcome to Our Hillbrow (2001) by Phaswane Mpe through the lens of Fanons’ concept of decolonization, and attributes the actions of xenophobic violence in South Africa to the incomplete process of decolonization after apartheid. The article concludes that unsuccessful liberation and incomplete decolonization can lead to a state of neo colonialism and ultimately, neo-apartheid. Xenophobic violence is triggered and motivated by the reality that nothing has really changed in South Africa even after the dismantlement apartheid.